2017
DOI: 10.1186/s13071-017-2211-8
|View full text |Cite
|
Sign up to set email alerts
|

Ecological parameters of the (S)-9-methylgermacrene-B population of the Lutzomyia longipalpis complex in a visceral leishmaniasis area in São Paulo state, Brazil

Abstract: BackgroundVisceral leishmaniasis (VL) is an important public health challenge in Brazil because of the high number of human and canine cases reported annually. Leishmania infantum is the etiological agent of VL and Lutzomyia longipalpis is its main vector. However, evidence suggests that this taxon constitutes a species complex. In Sao Paulo state, there are two populations of Lu. longipalpis, each secreting distinct pheromones, (S)-9-methylgermacrene-B and Cembrene 1; both have been associated with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
15

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 42 publications
1
24
0
15
Order By: Relevance
“…Em relação a variável precipitação pluviométrica, os clusters com alta precipitação e alta taxa de incidência, e clusters com baixa precipitação e baixa taxa demonstram a correlação espacial positiva entre essas variáveis. A variável precipitação pluviométrica, que se correlaciona com a umidade, favorece o desenvolvimento e reprodução do vetor e consequente aumento da incidência de LV 30,31,32 . Como Tocantins apresenta características do bioma Amazônia e do cerrado, com o bioma Amazônia ocorrendo mais ao norte do estado, o regime de chuvas da floresta tropical exerce forte influência na pluviosidade e consequente umidade do estado, contribuindo para incidência da LV nessa região do estado.…”
Section: Evi: íNdice De Vegetação Melhorado (Enhanced Vegetation Index)unclassified
“…Em relação a variável precipitação pluviométrica, os clusters com alta precipitação e alta taxa de incidência, e clusters com baixa precipitação e baixa taxa demonstram a correlação espacial positiva entre essas variáveis. A variável precipitação pluviométrica, que se correlaciona com a umidade, favorece o desenvolvimento e reprodução do vetor e consequente aumento da incidência de LV 30,31,32 . Como Tocantins apresenta características do bioma Amazônia e do cerrado, com o bioma Amazônia ocorrendo mais ao norte do estado, o regime de chuvas da floresta tropical exerce forte influência na pluviosidade e consequente umidade do estado, contribuindo para incidência da LV nessa região do estado.…”
Section: Evi: íNdice De Vegetação Melhorado (Enhanced Vegetation Index)unclassified
“…The estimated population size shows the high frequencies of Lu . longipalpis in this municipality in the rainy season as observed in a study with monthly captures in this focus [ 18 ] where females carrying eggs were also captured in the intradomicile. This information suggests that in this period the probability of contact between competent vector and infected and susceptible host increased.…”
Section: Discussionmentioning
confidence: 74%
“…Previous study in this locality had identified six sand fly species belonging to the Nyssomyia , Evandromyia , Brumptomyia and Lutzomyia genera, with the predominance of the (S)-9-methylgermacrene-B population of the Lu . longipalpis complex [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the New World the main vector is Lutzomyia longipalpis , a species adapted to sylvatic and rural [ 6 ], urban and peri-urban environments [ 7 ]. This vector species occurs from Mexico to Argentina [ 8 ] and is progressively expanding its distributional range in Brazil, Paraguay, Argentina [ 3 ] and Uruguay [ 4 ], and consequently expanding the risk for human and canine VL cases in these areas [ 8 ].…”
Section: Introductionmentioning
confidence: 99%